Increased expression of LD1 genes transcribed by RNA polymerase I in Leishmania donovani as a result of duplication into the rRNA gene locus. - Lodes, M J (1995)
Eukaryotic protein-coding genes are generally transcribed by RNA polymerase II (Pol II), which has a lower transcription rate than that of Pol I. We report here the duplication of two LD1 genes into the rRNA locus and their resultant transcription by Pol I. The multigenic LD1 locus is present in a 2.2-Mb chromosome in all stocks of Leishmania spp. and is also present in multicopy 200- to 450-kb linear chromosomes or multicopy circular DNAs in over 15% of stocks examined. Genomic rearrangement in Leishmania donovani LSB-51.1 resulted in duplication of a 3.9-kb segment of LD1 containing two genes (orfF and orfG) and of a 1.3-kb segment from approximately 10 kb downstream into the rRNA gene repeat region of the 1.2-Mb chromosome. Short sequences (12 or 13 bp) common to the 2.2-Mb LD1 and 1.2-Mb rRNA loci suggest that this gene conversion occurred by homologous recombination. Transcription of the duplicated genes is alpha-amanitin resistant, indicating transcription by Pol I, in contrast to the alpha-amanitin-sensitive (Pol II) transcription of the genes in the 2.2-Mb LD1 locus. This results in higher transcript abundance than expected from the gene copy number in LSB-51.1 and in elevated expression of at least the orfF gene product.